Defining paediatric metabolic (dysfunction)-associated fatty liver disease: an international expert consensus statement. (October 2021) - Eslam, Mohammed; Alkhouri, Naim; Vajro, Pietro; Baumann, Ulrich; Weiss, Ram; Socha, Piotr; Marcus, Claude; Lee, Way Seah; Kelly, Deirdre; Porta, Gilda; El-Guindi, Mohamed A; Alisi, Anna; et al.
Summary: The term non-alcoholic fatty liver disease (NAFLD), and its definition, have limitations for both adults and children. The definition is most problematic for children, for whom alcohol consumption is usually not a concern. This problematic definition has prompted a consensus to rename and redefine adult NAFLD associated with metabolic dysregulation to metabolic (dysfunction)-associated fatty liver disease (MAFLD). Similarities, distinctions, and differences exist in the causes, natural history, and prognosis of fatty liver diseases in children compared with adults. In this Viewpoint we, an international panel, propose an overarching framework for paediatric fatty liver diseases and an age-appropriate MAFLD definition based on sex and age percentiles. The framework recognises the possibility of other coexisting systemic fatty liver diseases in children. The new MAFLD diagnostic criteria provide paediatricians with a conceptual scaffold for disease diagnosis, risk stratification, and improved clinical and multidisciplinary care, and they align with a definition that is valid across the lifespan.